Effect of pre-germination time on amino acid profile and Gamma Amino Buytric Acid (GABA) contents in different varieties of Malaysian brown rice. - Roohinejad, Shahin; Omidizadeh , Alireza; Mirhosseini, Hamed; Saari, Nazamid; Mustafa, Shuhaimi; Meor Hussin, Anis Shobirin; Abdul Hamid, Azizah; Abd. Manap, Mohd. Yazid (Taylor & Francis, 2011)
Eighteen varieties of Malaysian brown rice were evaluated for their crude protein, total glutamic acid, and gamma amino butyric acid contents after pre-germination at different times. The crude protein and total glutamic acid content increased significantly in all the varieties after pre-germination. Gamma amino butyric acid content increased dramatically with time during the pre-germination process. A significant (p < 0.05) positive correlation was observed between protein, glutamic acid, and gamma amino butyric acid contents before and after pre-germination. The brown rice varieties containing higher glutamic acid and/or protein content before the pre-germination process provided more gamma amino butyric acid content during pre-germination.